Building to Start at Maritime School - Vallejo Times-Herald (Vallejo Times-Herald)
Construction of a new permanent type residence hall at the California Maritime Academy is slated to start within the next two weeks, the state Department of Public Works said today as it announced awarding of three construction contracts totaling $572,677.